A plant design on the production of coconut flour - Heruela, Conrado S. (College of Engineering, 1976)
Plant: Cocoflour -- Location: Southern Tagalog Region -- Annual capacity at maximum rate of production: coconuts 180,000,000 lbs, Hexane 23,760,000 lbs., cocoflour 13,200,000 lbs., cocowater 58,500,000 lbs., cocoshells 40,500,000 lbs., coco oil 24,576,000 lbs. -- Fixed capital investment: P 32,976,255 -- Annual manufacturing cost at maximum capacity: P 51,522,093 -- Working days: 300 days -- Breakeven point: 56% -- Shut/down point: 36% -- Pay-out time: 2.6 years